1999
DOI: 10.1007/s004230050207
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive videoscopic parathyroidectomy by lateral approach

Abstract: This preliminary study demonstrates that minimally invasive videoscopic parathyroidectomy by lateral approach is a feasible surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
9

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(86 citation statements)
references
References 10 publications
(9 reference statements)
1
75
0
9
Order By: Relevance
“…Most authors reported excellent results without any false positive findings [5, 6, 7, 8, 9]. A 50% decrease of the PTH value within 10 min after resection of the hyperfunctional parathyroid tissue is generally used to predict permanent normocalcemia [10]and reports of false positive QPTH measurements are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors reported excellent results without any false positive findings [5, 6, 7, 8, 9]. A 50% decrease of the PTH value within 10 min after resection of the hyperfunctional parathyroid tissue is generally used to predict permanent normocalcemia [10]and reports of false positive QPTH measurements are rare.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, to date the most widely used techniques are the video-assisted parathyroidectomy (VAP) with cervical central access first described by Miccoli et al [6] and VAP via the lateral approach proposed by Henry et al [7] . Because of its resemblance with conventional surgery, the possibility to perform a bilateral neck exploration when necessary and the possibility to freely modify the endoscope orientation through the skin incision, we chose to adopt in our surgical practice VAP by the central access.…”
Section: Introductionmentioning
confidence: 99%
“…The thyroid gland is approached laterally through splitting of strap muscle and SCM. Henry et al [15] first reported their technique on the endoscopic lateral approach in 1999. One 10-mm and two 3-mm ports were inserted along the SCM.…”
Section: Endoscopic Lateral Approachmentioning
confidence: 99%